2009
DOI: 10.17221/1724-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cycloheximide or 6-dimethyl aminopurine on the parthenogenetic activation of pig oocytes using pulsatile treatment with nitric oxide donor

Abstract: Pig oocytes matured in vitro were parthenogenetically activated using nitric oxide donor SNAP (2mM). Continuous treatment successfully activated the oocytes only after more than 12 hours of exposure. Pulsatile treatments during which oocytes were repeatedly exposed to 2mM SNAP for a short time (10, 20 or 30 minutes) were more efficient with regard to the activation rate, even when the total exposure time did not exceed 4 hours. Parthenogenetic development was very limited after continuous treatment with 2mM SN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 58 publications
(79 reference statements)
0
2
0
Order By: Relevance
“…In this study, Ca-EDTA treatment during maturation culture not only activated porcine immature oocytes but also induced parthenogenetic development to blastocyst stage. It had been shown that MII-stage oocytes can be parthenogenetically activated by artificial stimuli and that activated oocytes can cleave and develop to the blastocyst stage [ 12 , 13 ]. Historically, Azuma et al .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, Ca-EDTA treatment during maturation culture not only activated porcine immature oocytes but also induced parthenogenetic development to blastocyst stage. It had been shown that MII-stage oocytes can be parthenogenetically activated by artificial stimuli and that activated oocytes can cleave and develop to the blastocyst stage [ 12 , 13 ]. Historically, Azuma et al .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, NOS inhibition supresses cumulus expansion of sheep oocytes . The role of NO in oocyte activation and early embryonic development of fertilized or parthenogenetically activated oocytes was also studied (Goud et al, 2008;Krejčová et al, 2009). Although not essential for mouse oocyte fertilization (Hyslop et al, 2001), NO is able to activate the oocytes of pigs and amphibians (Petr et al, 2005Jeseta et al, 2012), presumably throughout cGMP and PKG signalling pathways (Petr et al, 2006).…”
mentioning
confidence: 99%